A novel low power method of combining saliency and segmentation for mobile displays - Suh, Simon; Hong, Seok Min; Kim, Young Jin; Park, Jong Sung (Electronics (Switzerland), 2021)
Saliency, which means the area human vision is concentrated, can be used in many applications, such as enemy detection in solider goggles and person detection in an auto‐driving car. In recent years, saliency is obtained instead of human eyes using a model in an automated way in HMD (Head Mounted Display), smartphones, and VR (Virtual Reality) devices based on mobile displays; however, such a mobile device needs too much power to maintain saliency on a mobile display. Therefore, low power saliency methods have been important. CURA tried to power down, according to the saliency level, while keeping human visual satisfaction. But it still has some artifacts due to the difference in brightness at the boundary of the region divided by saliency. In this paper, we propose a new segmentation‐based saliency‐aware low power approach to minimize the artifacts. Unlike CURA, our work considers visual perceptuality and power management at the saliency level and at the segmented region level for each saliency. Through experiments, our work achieves low power in each region divided by saliency and in the segmented regions in each saliency region, while maintaining human visual satisfaction for saliency. In addition, it maintains good image distortion quality while removing artifacts efficiently.
Keywords: Low power; Mobile display; Saliency; Segmentation